MADRASAS OF BUKHARA (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article describes the general name of Bukhara madrasahs - the general name of Bukhara madrasahs - educational institutions built specifically for providing higher education in the Bukhara oasis from the beginning of the 9th century, after the introduction of Islam to the territory of Turan, as well as the opinions of scholars who studied in them on religious issues in Egypt and Hijaz. The information is stated to be more reliable than the opinions of the readers.